LCA as a Complementary Tool for the Evaluation of Biocolonization Management: The Case of Palazzo Rocca Costaguta - Letizia Berti; Francesco Arfelli; Federica Villa; Francesca Cappitelli; Davide Gulotta; Luca Ciacci; Elena Bernardi; Ivano Vassura; Fabrizio Passarini; Salvatore Napoli; Sara Goidanich (Heritage)
The 17th Century Casa a Ponente of Palazzo Rocca Costaguta’s wall provided an opportunity for an evaluation based on a Life Cycle Assessment (LCA) approach of conservation treatments aiming at removing biological colonization from built heritage surfaces. The investigated surfaces were historic plasters partially covered by a patchy green patina due to biofilm recolonization soon after a previous biocidal treatment. Areas of the biocolonized wall were treated by conservation professionals according to both conventional and “green” (i.e., exploiting natural active principles) biocidal products, including Preventol RI 50 (active substance benzalkonium chloride), Essenzio (active substance essential oregano oil), and hydrogen peroxide. Upon treatment, LCA analysis was conducted to evaluate the environmental impact of the different solutions, including a no-treatment option. LCA analysis was based on on-site investigations of the untreated wall surface with and without biofilm and following the biocidal treatment. The conservation treatment’s impact on the mineral substrate was based on digital microscopy, colorimetry, and water contact angle measurements via an innovative portable method. The results highlighted the impacts of the different biocidal treatments, which, in some cases, have not completely removed the biofilm and, in some cases, have altered the surface properties of the plaster. This pointed out the opportunity to re-think conservation strategy, including LCA analysis as a complementary tool to assess the environmental impact of the different conservation treatments and procedures.